The Impact of Lecturer Performance Management on Higher Education Graduate Quality - Asmawati, Asmawati; Wasliman, Iim; Sulatini, Rita; Rosmaladewi, Okke (Lectura : Jurnal Pendidikan, 2025)
The management of lecturer performance in higher education has not been optimally implemented, thus impacting the quality of graduates. This study aimed to provide a comprehensive analysis of lecturer performance management to enhance graduate quality. Specifically, it explores the planning, organization, implementation, evaluation, and challenges of lecturer performance management along with the proposed solutions. Adopting a qualitative approach with a case study method, data was collected through observations, interviews, and document analysis and subsequently analyzed using triangulation techniques. This study is grounded in Terry’s management theory, Veithzal R’s performance theory, and Sallis’ quality theory. The findings reveal that: (1) performance planning focuses on the implementation of the Tridharma of Higher Education, reinforcing lecturers’ commitment to their professional responsibilities; (2) task and workload distribution follow applicable regulations; (3) performance implementation aligns with the university’s vision, mission, and strategic plans; (4) performance evaluation is conducted by university leadership with the involvement of the Quality Assurance Team; (5) key challenges include suboptimal lecturer performance, financial management issues, and inadequate facilities; and (6) proposed solutions encompass enhancing lecturer competencies, improving financial management, and upgrading infrastructure. In conclusion, although lecturer performance management has been implemented effectively, continuous improvements are necessary to further enhance graduate quality.